The Rise and the Future of Militias in the Mena Region - Tarik M. Yousef (Pubblicazioni ISPI, 2020)
In recent decades, militias and sub-national armed groups have played a decisive role in politics and security in the MENA region. Their prominence with local and outside actors in areas where state institutions have collapsed presents multiple policy challenges. Armed groups have access to substantial resources and in some cases enjoy considerable local legitimacy. That makes them formidable but also resilient forces. This is why their suppression - through coercive measures or marginalization - can bring more costs than benefits to already fragile state institutions and exhausted populations. This volume addresses the void in the current debate on subnational armed groups, focusing particularly on the multiple ongoing conflicts and turmoil in the MENA region. It places a particular emphasis on whether armed groups can be integrated into state-building initiatives and whether they can play a constructive role with other key actors.